Evaluating Customer Preferences For Human Resources At Ayam Kosek Restaurant: A Comparative Study Based On SERVQUAL Dimensions - Agung Edy Wibowo; Kartika Cahayani; Asman Abnur; I.Nyoman Budhiartha; M.Irfan Fitrian (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2026)
This study aims to analyze customer preferences toward human resources (HR) quality in a restaurant operating across three different locations using the Service Quality (SERVQUAL) approach. Human resources play a critical role in the restaurant industry because they directly influence service experiences that affect customer satisfaction and loyalty. Service quality in this study was evaluated based on the five SERVQUAL dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The research employed a quantitative approach involving 99 respondents selected through purposive sampling. The respondents consisted of customers who had previously visited and received services directly from the restaurants under study. Data were collected through structured questionnaires and analyzed using descriptive statistics and comparative tests to determine whether differences existed in customer preferences regarding HR quality across the three restaurant locations. The findings reveal that each location obtained different mean scores across several SERVQUAL dimensions. These differences indicate variations in customer perceptions regarding the performance of employees at each restaurant branch. However, statistical testing demonstrated that the observed differences were not statistically significant. This result suggests that the quality of service delivered by human resources across the three restaurant locations is relatively consistent and capable of meeting customer expectations at a comparable level. Therefore, despite the existence of differences in average scores among locations, customers generally do not exhibit significantly different preferences regarding the quality of human resources serving them. The study implies that the service standards implemented by the restaurant management have been applied relatively uniformly across all branches. These findings provide valuable insights for management in maintaining service consistency while continuously improving employee performance and service quality. Furthermore, the results highlight the importance of sustaining standardized service practices as a strategic effort to strengthen customer satisfaction, enhance customer loyalty, and improve the restaurant’s competitiveness in an increasingly dynamic and competitive market environment